The effect of microbial load and water recycling on the flotation performance of a PGM bearing ore - Wabatagore, Vushe (Department of Chemical Engineering, 2022)
Mineral processing requires large quantities of water for its operations. With the continuing move to reduce freshwater withdrawal and mine water discharge, the mineral industry has been applying water recycling and reuse to improve water use efficiency. Previous studies on the use of remediated water as supplementary point source water and water recycling within the flotation circuit have shown that these practices affect the flotation process performance. It is therefore important to understand the effect that components within recycled and reclaimed water may have on flotation performance. While research on the effects of the abiotic components such as ions on flotation is well represented in literature, the effects of biotic water components, particularly microorganisms, on flotation performance still remain understudied and poorly understood. This study aimed to contribute to our understanding of the effects microbes have on the flotation performance of a PGM bearing ore from the Bushveld IgneousComplex in South Africa. In addition, the effects of xanthate collectors such as Sodium Ethyl Xanthate (SEX) and Sodium Isobutyl Xanthate (SIBX), widely employed in sulphide mineral beneficiation, on microbial growth were also considered. Results suggest that the presence of microbial cells and recycling of flotation waters increase water and solids recovery, while the metal grade recoveries were negatively affected. The microbial community used in this study could proliferate in the presence of up to 240 ppm for SEX and 480 ppm for SIBX, with an increase in the lag phase of growth observed with increasing collector concentrations. The presence of microbes at a concentration of 109 cells/ml resulted in the compete removal of 60 ppm collector from solution, both SEX and SIBX, from solution within a 2-hour time period. Outcomes of this study include a method for the measurement of microbial activity within a mineral slurry, which will further facilitate studying the effects of microorganisms on flotation systems. The work presented in this dissertation revealed that the presence of microbial consortia studied here negatively affected metal (Cu and Ni) grades attesting to the detrimental effect posed by the usage of microbial laden water for flotation operations. Further, the microbial consortium showed that it can facilitate the bioremoval of xanthate from solution which could affect the recovery of valuable minerals during flotation operations. This mechanistic framework, explaining the mechanisms by which the microbes affect flotation and the detrimental effects posed by microbes found in flotation waters is an actionable (fundamental) for the mining industry. From the present study, it is recommended that researchers should assess the microbial load present in flotation waters prior to their usage for flotation operations as high microbial load proved to be detrimental as far as flotation performance is concerned on a laboratory scale. Conclusively, the knowledge generated from this study builds on the ongoing scientific efforts decoding the effects of naturally prevailing microbes in flotation waters.